THE INFLUENCE OF PROMOTION AND TRUST ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION - Widodo, Aris; Murwatiningsih, Murwatiningsih (Management Analysis Journal, 2019)
The purpose of this research is to examine between promotion and trust toward customer loyalty through customer satisfaction as mediating role. The population in this research is all TCash users in Semarang City. The numbers of sample in this research are 115 respondents by using incidental sampling. Path analysis is used for analyzing the research data using SPSS program version 21. The results findings are both promotion have a positive and significant on customer loyalty, and  trust have a positive and significant on customer loyalty, and customer satisfaction is able to mediate between promotion and trust in customer loyalty.